Analisis Pengaruh Variabel Makroekonomi Terhadap Pertumbuhan Ekonomi di Indonesia - Efendi, Alwindo; Aimon, Hasdi (Universitas Negeri Padang, 2024)
This research aims to determine and analyze the influence of inflation, investment and net exports on economic growth in Indonesia. This research is quantitative with time series data in Indonesia from 1990-2023. The data that researchers used in this research is secondary data obtained from the National Statistics Agency, Indonesian Bank and the International Monetary Fund (IMF). The results of this research show (1) the inflation variable has a nonlinear influence on economic growth, (2) the investment variable has a positive and significant influence on economic growth, ( 3) the net export variable has a positive and significant influence on economic growth, (4) the inflation, investment and net export simultaneously have a significant influenceon economic growth in Indonesia